Yupingfeng polysaccharides enhances growth performance in Qingyuan partridge chicken by up‐regulating the mRNA expression of SGLT1, GLUT2 and GLUT5 - Fuquan Yin; Ruixia Lan; Zhengmin Wu; Zhijing Wang; Haohao Wu; Zhiming Li; Hui Yu; Zhihui Zhao; Hua Li (Veterinary Medicine and Science, 2019)
Abstract The ban on the use of antibiotic in feed encouraged nutritionists to using alternatives to maintain growth performance and intestinal function of broilers. This study was conducted to evaluate the effects of Yupingfeng polysaccharides (YP) supplementation on growth performance and expression of SGLT1, GLUT2 and GLUT5 in Qingyuan partridge chicken. Experiment 1: a total of 540 chickens were randomly allocated to five groups with six replication. Dietary treatments were: (1) CON (control group), basal diet; (2) T1, CON + 0.5 g kg−1 YP; (3) T2, CON + 1 g kg−1 YP; (4) T3, CON + 2 g kg−1 YP; (5) T4, CON + 4 g kg−1 YP. Experiment 2, a total of 162 were randomly allocated to three groups with three replication. Dietary treatments were: (1) CON, basal diet; (2) T1, CON + 0.5 g kg−1 YP; (3) T2, CON + 1 g kg−1 YP. From days 1 to 14 and overall, chicken fed T1 diet had higher ADG. On day 42, there was increased villus height of jejunum in T1 group. On days 14 and 28, there was decreased villus height of duodenum and jejunum in T2 group. In duodenum, the expression of SGLT1 (days 21, 35 and 42), GLUT2 (days 7, 14, 21, 28, 35 and 42) and GLUT5 (days 7, 14, 21 and 28) was increased with YP supplementation. In jejunum, the expression of SGLT1 (days 7, 14, 21, 28 and 35), GLUT2 (days 14, 21, 28, 35 and 42) and GLUT5 (days 7, 14, 21, 28, 35 and 42) was increased with YP supplementation. In ileum, the expression of SGLT1 (days 7, 21, 35 and 42), GLUT2 (days 7, 14, 21 and 42) and GLUT5 (days 7, 14, 21, 28, 35 and 42) was increased with YP supplementation. Dietary YP supplementation improves growth performance and expression of SGLT1, GLUT2 and GLUT5 in intestine.